HUBUNGAN DUKUNGAN KELUARGA DENGAN PERILAKU PENCEGAHAN COVID19 PADA LANSIA DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU - Nur’aina Nur’aina; Arneliwati Arneliwati; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Covid-19 is a group of viruses that attacks the respiratory tract. Elderly people are more susceptible to exposure to covid-19 because they experience decreased function and immunity. The vulnerability of covid-19 to attacking the elderly needs to take precautions to reduce the risk of the elderly being exposed to this virus. Good preventive behavior requires family support because the elderly experience physical limitations in carrying out activities. Family support is one of the factors that influence the elderly in conducting covid-19 prevention behavior. This study aims to determine the relationship between family support and covid-19 prevention behavior in the elderly. The research design used was descriptive correlation with cross sectional approach. The sampling method used was purposive sampling, with a sample size of 98 respondents according to the inclusion criteria. The results showed that the majority of research subjects were 60-69 years old as many as 70 respondents (71,4%), female as much as 51 respondents (52%), as many as 38 respondents (38,8%) of junior high school education. The work of housewives (IRT) was 50 respondents (51%). Marital status is married as many as 70 respondents (71,4%). The results of chi square test showed that p value (0.000) < α (0.05) concluded that there was a significant relationship between family support and covid-19 prevention behavior in the elderly.Keywords: family support, behavior, elderly